Nurturing the other first contacts and the making of Christian bodies in Amazonia - Grotti, Vanessa Elisa (Berghahn, 2022)
Combining archival research, oral history and long-term ethnography, this book studies relations between Amerindians and outsiders, such as American missionaries, through a series of contact expeditions that led to the 'pacification' of three native Amazonian groups in Suriname and French Guiana. The author examines and contrasts Amerindian and non-Amerindian views on this process of social transformation through the lens of the body, notions of peacefulness and kinship, as well as native warfare and shamanism. The book addresses questions of change and continuity, and the little explored links between first contacts, capture and native conversion to Christianity in contemporary indigenous Amazonia